Leveraging technology to support HELINA Education Working Group activities - Jaafa, Noah Kasiiti; Centers, Kristin; Gesicho, Milka; Verbeke , Frank; Yeung , Ada; Nyangena, Job; Karanja, Eva; Were , Martin (Journal of Health Informatics in Africa, 2022)
Background and Purpose: Working groups implementing activities for health informatics associations need the right technological infrastructure to support the range of activities they conduct. In this paper, we describe the approach taken and results achieved in developing the technology-based infrastructure to support HELINA Education Working Group activities. Methods: Technological infrastructure needs for the EWG were guided by work sets for the WG. In collaboration with the technical team, the technology tools were identified with a bias towards open-source tools. The waterfall model was used for the development of needed features. Results: Tools implemented to support the HELINA EWG included a website (HELINAnet), a discussion forum (HELINAtalk), an eLearning and content organization platform (HELINALearn), social media accounts (Twitter, LinkedIn, and Facebook), a video conferencing platform based on Zoom, an email-based google mailing list (helina-ewg@googlegroups.com), and an electronic newsletter. Metrics of use were maintained. Conclusions: The approach taken to implement the technological infrastructure to support EWG activities can serve as a demonstrative model that could be employed by other HELINA WG, as well as the larger organization. Keywords: Health Informatics, Education, Working Group, Technology